A broadband out‐of‐phase gysel power divider based on a dual‐band circuit with a single fixed isolation resistor. Issue 9 (17th August 2016) - Mohammad Hadi Mousavi, Seyed; Salar Rahimi, Marzieh; Malakooti, Seyed‐Ali; Afzali, Behnam; Singh Virdee, Bal
Abstract: Based on the double‐sided parallel‐strip lines with an inserted conductor as a virtual ground, a high power divider with dual‐band/broadband response and frequency‐independent 180° phase difference between the output ports is implemented in this paper. The circuit topology employs a single commercially available external isolation resistor as well as moderate line impedances (15–100 ohm), making it suitable for high‐power applications. Precise closed‐form design equations on the basis of even‐ and odd‐mode analysis are derived. In addition to the wide range of frequency band ratios from 1 to 2.65, broadband response is also obtained by selecting the proper value of frequency band ratios. To substantiate the design equations and theory, a circuit with 2:1 frequency ratio and 84.5% bandwidth referring to 16 dB isolation and 12 dB return loss values is developed. To the authors' knowledge, this is the widest bandwidth reported for out‐of‐phase high power dividers. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2016.